Membangun Generasi Emas dengan Variasi Model Pembelajaran Aktif dan Inspiring - Nur Khomisah Pohan; Ihsanul Amin Muda Ritonga (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
With various active and inspiring learning techniques, this study tries to understand and build the golden generation. The data collection approach is a library research method, including evaluation and exploration of various journal articles, books, and other data or information sources that are considered important for this topic. The active and aspiring learning model in the golden age is a very important learning model to be utilized in this golden era, according to the findings of this study. This stimulates participants, according to Nizam. According to him, higher education is a place for innovation and synthesis of knowledge, while welcoming the Golden Indonesia 2045. Teachers or lecturers will not be the only focus of learning.